Word Sense Ambiguation: Clustering Related Senses - Dolan, Bill (Association for Computational Linguistics, 1994)
This paper describes a heuristic approach to automatically identifying which senses of a machine- readable dictionary (MRD) headword are semantically related versus those which correspond to fundamentally different senses of the word. The inclusion of this information in a lexical database profoundly alters the nature of sense disambiguation: the appropriate "sense" of a polysemous word may now correspond to some set of related senses. Our technique offers benefits both for on-line semantic processing and for the challenging task of mapping word senses across multiple MRDs in creating a merged lexical database.
Proceedings of the Eleventh Conference on Uncertainty in Artificial Intelligence (UAI1995)